Karya Tari Kontemporer Butterfly Hug - Tanalepy, Nada Lunetta Laura; Padmini, Tjok. Istri Putra; Kustiyanti, dyah (UPT Pusat Penerbitan LP2MPP Institut Seni Indonesia Denpasar, 2024)
The contemporary dance named Butterfly Hug is a type of dance study that originated from the creator's fascination with psychology that combined with art of dance. The inspiration behind this dance stems from the butterfly hug psychotherapy method. This dance emphasizes movements that the cross-shaped actions and the essence of embracing and patting, while doing the butterfly hug method. For the pursuit of the Merdeka Belajar – Kampus Merdeka (MBKM) Study/Project Independent program, the creator partnered with the Wayan Geria Foundation (GEOKS). The creation process of this dance adheres to the Alma Hawkins method, progressing through three distinct stages: exploration, improvisation, and forming. Comprising seven female dancers, the group performance spans a duration of 12 minutes. Crafting movements that exude creativity and sensitivity posed challenges in composing a piece that avoids monotony. Through this work, the creator aspires to offer a fresh perspective, especially within the artistic realm, by amalgamating two diverse disciplines to produce a unique artwork.